Metagenomic analysis and biodiversity of Lactic Acid Bacteria (LAB) on masin (fermented sauce) from Sumbawa, West Nusa Tenggara, Indonesia - Baso Manguntungi; Dinar Saputri; Apon Mustopa; Nurlaili Ekawati; Chairul Afgani; Arlindah Sari; Lita Triratna; Linda Sukmarini; Fatimah FATIMAH; Amirin Kusmiran; SAHRI YANTI; Shasmita Irawan; Muhammad Prasetyo; Khadijah ALLIYA Fidien (Society for Indonesian Biodiversity, 2020)
Abstract. Manguntungi B, Saputri DS, Mustopa AZ, Ekawati N, Afgani CA, Sari AP, Triratna L, Sukmarini L, Fatimah, Kusmiran A, Yanti S, Irawan S, Prasetyo MD, Fidien KA. 2020. Metagenomic analysis and biodiversity of Lactic Acid Bacteria (LAB) on masin (fermented sauce) from Sumbawa, West Nusa Tenggara, Indonesia. Biodiversitas 21: 3287-3293. Masin is a spontaneously fermented sauce from Sumbawa, West Nusa Tenggara Indonesia that is made of shrimp paste, chili, turmeric flower, and herbs mixed with some spices. This study aims to isolate Lactic Acid Bacteria (LAB) and analyze the metagenomic and biodiversity of its bacteria. Genome isolation for metagenomic analysis was using ZymoBIOMICSTM DNA Miniprep Kit. Sequencing analysis to identify LAB strain form masin was using 16S rRNA universal primer. Metagenomic analysis showed that relative abundance bacteria in masin for order taxon was Lactobacillales, the family taxon was Enteroccocaceae, and the genus was Tetragenoccocus. Six different groups were obtained from the phylogenetic tree analysis of 40 isolates found in masin. The representatives of each group taken were isolates number 2, 17, 11, 34, 28,  and 5. Based on the results of sequencing analysis, the 6 isolates found in masin are Staphylococcus piscifermentans strain CIP103958 (Isolate Code 2), S. piscifermentans strain BULST54 (Isolate Code 17), S. piscifermentans strain SK03 (Isolate Code 11), S. piscifermentans strain ATCC 51136 (Isolate Code 34), S. piscifermentans strain PCM 2409 (Isolate Code 28) and S. piscifermentans strain PU-87 (Isolate Code 5). Through this research, it has been described a whole diversity of bacteria contained in masin, one of them is Lactic acid bacteria. The six LAB isolates that have been identified can be developed as starter candidates for masin production.